Molecular Dynamics Simulation of the Nanoindentation of Coal Vitrinite - Liu, Hewu; Hou, Chenliang; Song, Yu (Frontiers in Earth Science, 2022)
Coal deformation is closely correlated with the distribution of organic maceral groups; however, molecular dynamics (MD) simulations of vitrinite nanoindentation have rarely been conducted. In this study, the vitrinite substrate for indentation was constructed utilizing polymer consistent force field (PCFF), and a spherical ghost indenter was used for loading. The results showed that: (1) In the indentation process, some of the vitrinite atoms overcame the energy barrier to move, with the most important deformation mechanism including the sliding, bending, and reorientation of vitrinite molecular chains, leading to the formation of a shearing transformation zone (STZ), which was also found to contain structural defects and stacking of aromatic structures. (2) The distribution of atomic displacements in the vitrinite substrate could be subdivided into distinct regions, with slippage at the region boundaries producing shear bands. (3) The surface morphology and mechanical properties obtained from the nanoindentation simulation were similar to experimental results from the literature, indicating that MD simulations are a powerful tool for studying coal nanoindentation. The results from this study increase the current scientific understanding of the mechanical properties of vitrinite by providing a new perspective that elucidates the nanoscale structural evolution occurring during the indentation process.